Morphology, Morphometrics, and Shark Conservation Status at TPI Sibolga City, North Sumatra Province - Tatanagara, Muhammad Ilham; Amin, Bintal; Samiaji, Joko (Journal of Coastal and Ocean Sciences, 2022)
Sharks are predatory animals that dwell near coral reefs and swim at the ocean's bottom. Since the inclusion of many shark species in CITES Appendix II status in 2013, shark groups have become a global issue. This is owing to shark fishing's high exploitation, both as a target capture and as bycatch. It is divided into eleven fisheries management areas, one of which is WPPNRI 572, according to the Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 18/PERMEN-KP/2014 concerning the State Fisheries Management Area of the Republic of Indonesia, hereinafter abbreviated as WPPNRI. The Indian Ocean waters west of Sumatra, as well as the Sunda Strait, are included in this area. Because it faces the high seas, notably the Indian Ocean, Sumatra's west coast is a key area of the Indonesian sea. The city of Sibolga is strategically important as one of the key entry points for utilizing the potential of western Sumatra's waters. This study was place during August and September of 2021. The goal of this study was to identify sharks landed through TPI Sibolga City in North Sumatra Province, describe their morphology and morphometrics, and describe their conservation status using IUCN and CITES criteria. Squalus chloroculus, Nebrius ferrugineus, Carcharhinus brevipinna, Carcharhinus falciformis, Carcharhinus melanopterus, Carcharhinus sorrah, Rhizoprionodon acutus, Rhizoprionodon oligolinx, and Sphyrna lewini were among the 310 sharks successfully landed in the TPI, according to the study's findings. The overall length variable has the strongest tendency, according to the results of the Principal Component Analysis Scree Plot. C. brevipinna, C. falciformis, C. melanopterus, C. sorrah, and T. obesus are shark species with comparable morphometric features. According to the IUCN, the conservation status of S. lewini is Critical or Threatened (EN). The status of N. ferrugineus is Very Vulnerable (VU). Near Threatened (NT) status for S. chloroculus, C. brevipinna, C. falciformis, C. melanopterus, C. sorrah, and T. obesus. Less Worrying Status was assigned to R. acutus and R. oligolinx (LC). While the trading status of sharks based on CITES, particularly C. falciformis, C. melanopterus, and S. lewini, are included in the Appendix II list, which denotes species that are not threatened with extinction but could be affected if trade continues without regulation.